2D Forward Modeling of Marine Controlled Source Electromagnetic (CSEM) Data for Salt-Dome and Stratigraphy Trap Reservoir - Hussain, Nazabat (2012)
The main elements of hydrocarbon saturated reservoirs are identified by using various geological survey techniques. For many years, marine Controlled Source Electromagnetic (CSEM) method is effectively being used for detection and observation of hydrocarbon reserves, either in shallow or deep water exploration. In this paper, 2D forward modeling is used to study electromagnetic (EM) field behavior in salt dome trap reservoir and stratigraphy trap reservoir. In this paper, we employs 2D forward modeling algorithm using finite difference (FD) method and finite element (FE) method to solve EM-field governing equations. The solution is achieved through i) applying staggered scheme for FD method, and ii) Galerkin scheme for Finite Element (FE) method. Both schemes used the optimal grid technique that extends the boundaries of the mesh outward from the region of interest using a minimal number of nodes, and direct matrix solution technique that allows for simultaneous solution for all sources. Results obtained for salt dome trap and stratigraphy trap shows the discrimination of EM signal for reservoir filled with hydrocarbon and without hydrocarbon. The obtained results can be used to verify the inversion of marine CSEM data.